Controlling the Integration of Economic Projects in Algerian Law - Makrof, Mohamed; Belouadah, Tayeb (Journal of Legal Studies and Researches, 2023)
This study aims to clarify the nature of control over the Integration of economic projects. This is one of the most important forms of the phenomenon of economic concentration, Therefore, jurists and economists were interested in the subject because of the revenues that these projects achieve, as well as the financial and fiscal support achieved by the merger.